EFFECT OF LEAD ON THE SKIN AND HEALTH OF FEMALE DERMATITIS PATIENTS THROUGH COSMETICS - Afridi, Hassan Imran; Ali, Asim; Bhatti, Murk; Unar , Ahsanullah; Chanihoon, Ghulam Qadir; Talpur , Farah Naz; Kazi , Tasneem Gul; Arain, Faisal Ali (Journal of Ayub Medical College Abbottabad, 2023)
Background: Cosmetics have been a part of routine body care not only for the upper classes but also for the middle and lower classes since the dawn of civilization. Cosmetic formulations are in more demand as the public’s interest in skin whitening grows. The contamination of cosmetics with heavy metals is a major concern as they containing heavy metals and pose a major risk to human health. This study looks in to the effects of Lead on human skin. Methods: in this cross-sectional study different products were examined. The matrices (scalp hair, blood, serum and nails) of reference and dermatitis cosmetic female patients (seborrhoeic dermatitis, rosacea, allergic contact dermatitis, and irritant contact dermatitis) and cosmetic samples were used in a 2:1 mixture of HNO3 (65%) and H2O2 (30%), and oxidation was performed using a microwave. The oxidized beauty and biological specimen underwent electrothermal atomic emission spectrophotometry after microwave-assisted acid digestion. The validity and precision of the methodology were verified using certified reference materials. Cosmetic products (lipstick, face powder, Eye Liner and Eye shadow) of different brands contain Pb concentrations in the ranges of 50.5-120 Î¼g/g, 14.6-30.7 Î¼g/g, 2.87-4.25 Î¼g/g and 15.3-21.6 Î¼g/g, respectively. Results: In the present study, cosmetic products (lipstick (N=15), face powder (N=13), eye liner (N=11), eye shadow (N=15) and female patients with dermatitis (N=252) residing in Hyderabad city, Sindh, Pakistan, was investigated. The outcome of this investigation showed significantly higher levels of Pb in biological samples (blood and scalp hair) of different types of female dermatitis patients than in reference subjects (p<0.001). Conclusion: The cosmetic products, especially with regard to heavy metals adulteration, are in use by the female population.